Gender Differences in the Effect of Chronic Illness on Employment Status in Kenya - Phyllis Mumia Machio (European Scientific Journal, ESJ, 2016)
The burden of illness in Kenya has been high and rising with chronic illness becoming an important contributor to disease burden. Grossman (1972) viewed stock of health as an investment good that determines total healthy time available for market activities. Illness, therefore, can reduce total amount of healthy time causing individual’s to prefer flexible types of employment. This study estimates the effect of chronic illness on probability of participating in various type of employment in Kenya using the Kenya integrated household budget survey data. Multinomial probit models were used to model choice between wage employment, non-agricultural self- employment, agricultural self-employment and not working since data did not support the multinomial logit’s assumption of IIA. The results indicated that compared to not working, chronic illness reduced likelihood of individuals working in wage employment and in agricultural self-employment. When the analysis was disaggregated by gender, results showed that while chronic illness significantly reduced women’s likelihood of working in wage employment and in agricultural self-employment, it did not significantly influence men’s choice of employment type. Policies need to be put in place by the government to control the up rise in chronic illnesses. This can be through promotion of health lifestyles by advocating for consumption of healthy diets, physical activity and non tobacco consumption. The government can ensure proper management of chronic illnesses such as HIV/AIDS, diabetes, high blood pressure by making available at subsidized prices management drugs. Reducing chronic illness incidences not only increases utility of the individuals, but also affect labor market choices.